2020
DOI: 10.7759/cureus.8116
|View full text |Cite
|
Sign up to set email alerts
|

Biloma: A Rare Manifestation of Spontaneous Bile Leak

Abstract: A biloma is an intrahepatic or extrahepatic encapsulated collection of bile outside of the biliary tree and within the abdominal cavity. Hepatobiliary interventions and laparoscopic cholecystectomy are the most common etiologies of biloma followed by abdominal trauma, choledocholithiasis, and biliary dilation secondary to biliary stricture. We report a case of a 91year-old female who presented to the emergency room with an acute onset of epigastric and right upper quadrant sharp pain for one day that radiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 17 publications
0
22
0
9
Order By: Relevance
“…Existem algumas inconsistências na literatura quando se trata da definição de fístulas biliares espontâneas 5 . Alguns estudos definem como vazamento de bile onde uma causa específica permanece não identificável e geralmente é diagnóstico de exclusão 5,11 .…”
Section: Discussionunclassified
“…Existem algumas inconsistências na literatura quando se trata da definição de fístulas biliares espontâneas 5 . Alguns estudos definem como vazamento de bile onde uma causa específica permanece não identificável e geralmente é diagnóstico de exclusão 5,11 .…”
Section: Discussionunclassified
“…However, a large body of research defines bile leak as a broader term. Using the PubMed search function, a significant amount of literature was found that referred to "spontaneous bile leak," a term used to refer to a leakage of biliary fluid that did not follow surgical intervention of any kind [4,[9][10][11][12][13]. Spontaneous bile leak has been defined as a bile leak "where a specific cause remains unidentifiable and is usually a diagnosis of exclusion" [9].…”
Section: Discussionmentioning
confidence: 99%
“…Using the PubMed search function, a significant amount of literature was found that referred to "spontaneous bile leak," a term used to refer to a leakage of biliary fluid that did not follow surgical intervention of any kind [4,[9][10][11][12][13]. Spontaneous bile leak has been defined as a bile leak "where a specific cause remains unidentifiable and is usually a diagnosis of exclusion" [9]. One article presented a case similar to ours, of a spontaneous bile leak with no recent surgery, abdominal trauma, or evidence of cholelithiasis or sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient underwent MRCP that found a large epigastric cystic mass full of leaking bile, without any signs of CBD injury. Abdominal imaging, such as abdominal ultrasound (US), multi-slice computed tomography (MSCT), magnetic resonance cholangiopancreatography (MRCP), and Chole-scintigraphy using 99mTc hepatobiliary iminodiacetic acid (HIDA) scan, are crucial to identify biloma and rule out other possible etiologies [ 10 ]. Ultrasound (US) is preferable as the first-level imaging method, since it is non-invasive, fast and easy to perform.…”
Section: Discussionmentioning
confidence: 99%
“…But the sensitivity of abdominal US is low (70%), though it is used as the initial imaging in the evaluation of biloma. The sensitivity and specificity of CT scan are approximately 90% and those of MRI are above 95% in the detection of biloma and bile leak; however, smaller bilomas can be missed [ 4 , 10 ]. The MRCP sequences are helpful to identify the source of the biliary leak.…”
Section: Discussionmentioning
confidence: 99%